2020
DOI: 10.1017/s0954422420000189
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, low diet quality and its risk factors among older adults with low socio-economic status: a scoping review

Abstract: Low socioeconomic status (SES) is often associated with various health related problems. Therefore, this paper aims to review the available literatures to identify the prevalence of malnutrition, prevalence of poor diet quality and its associated risk factors among older adults with low SES. A literature search was performed using four databases namely PUBMED, Google Scholar, Springer and Science Direct. The search terms used were “diet quality”, “nutritional status”, “dietary intake”, “overweight”, “obesity”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A dichotomous outcome variable of overweight or obese (overweight/obese) was established and coded as follows: underweight/normal (BMI < 24.99) = 0, and overweight/obese (BMI > 25) = 1. Underweight is typically a risk factor associated with other health issues, since the purpose of this study was to focus on individuals with overweight or obese, we categorized underweight and normal as one reference group ( Nazri et al, 2020 ).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…A dichotomous outcome variable of overweight or obese (overweight/obese) was established and coded as follows: underweight/normal (BMI < 24.99) = 0, and overweight/obese (BMI > 25) = 1. Underweight is typically a risk factor associated with other health issues, since the purpose of this study was to focus on individuals with overweight or obese, we categorized underweight and normal as one reference group ( Nazri et al, 2020 ).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Older adults are more prone to nutritional problems, including undernutrition, due to various mechanisms [ 5 ]. Undernutrition in the older adult is most likely to be caused or exacerbated by acute and chronic diseases, depression, social isolation, and socioeconomic factors and is also accelerated by the aging process [ 6 , 7 , 8 , 9 , 10 , 11 ]. Moreover, long-term weight loss has been associated with cognitive impairment in middle-aged and older Japanese individuals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that compared to individuals with low genetic predispositions, individuals with high genetic obesity tendencies have a higher risk of developing esophageal cancer, and early screening for obesity should be strengthened [ 36 , 37 ]. In low-middle SDI areas and low SDI areas, the risk of chewing tobacco and diet is relatively high, which may be related to population and social economy [ 38 ]. Because there are obstacles in eliminating risk factors, it is difficult to achieve primary prevention.…”
Section: Discussionmentioning
confidence: 99%